Radiographic anatomy and imaging of the acetabulum. Issue 2 (April 2022) - Chotai, Neil; Arshad, Homa; Bates, Peter
Abstract: Imaging of the acetabulum in the trauma patient can be challenging but includes a number of well-established techniques. These include plain anteroposterior radiographs, 45° oblique Judet views, CT scanning and intraoperative fluoroscopy. An understanding of Letournel's lines is essential for the characterization of acetabular fractures from plain radiographs. A number of named features, for example the 'gull sign' and the 'spur sign' correlate with specific traumatic pathology. We define the role of CT scanning and describe the methods and potential utility of intraoperative fluoroscopy in acetabular trauma.